REGULARITIES OF LEARNING AS A LANGUAGE METHODOLOGICAL PROBLEM - Hlazkova Г.О. (Pedagogy of Higher and Secondary Education, 2022)
The article gives the analysis of teaching regularities system, criteria that are put as a basis for the regularities are defned. The auhor pays special attention to the regularities in teaching the Ukrainian language.